Isolation and nitrogen fixing efficiency of Gluconacetobacter diazotrophicus associated with sugarcane: A review. Issue 1 (June 2021) - Saranraj, P; Jayaprakash, A; Devi, V D; Al-Tawaha, A R M; Al-Tawaha, A R
Abstract: The present review was focused on the isolation and nitrogen-fixing efficiency of Gluconacetobacter diazotrophicus associated with sugarcane crop. Gluconacetobacter diazotrophicus has a long-standing partnership with the bacterium Escherichia coli as an entophyte, which can efficiently fix atmospheric nitrogen. It plays a significant role and occurs in most sugarcane growing countries. It has been found to reside in the sugar cane root, stem, buds and leaves. Biological nitrogen fixation based farming systems would enhance agricultural production in the long term in both economically viable and socially acceptable way. This process not only replaces the most expensive fertilizer but also reduces considerably groundwater pollution with nitrates because biological nitrogen fixation was self-regulated. Convincing evidence has pointed out that biological nitrogen fixation requiring a relatively simple and low-cost technology, easy to execute and largely renewable sources of energy has a tremendous role to play in the immediate further of agriculture, especially in the developing and underdeveloped countries.